Developmental Analysis of Mimulus Seed Transcriptomes Reveals Functional Gene Expression Clusters and Four Imprinted, Endosperm-Expressed Genes - Flores-Vergara, Miguel A.; Oneal, Elen; Costa, Mario; Villarino, Gonzalo; Roberts, Caitlyn; De Luis Balaguer, Maria Angels; Coimbra, Sílvia; Willis, John; Franks, Robert G. (Frontiers in Plant Science, 2020)
The double fertilization of the female gametophyte initiates embryogenesis and endosperm development in seeds via the activation of genes involved in cell differentiation, organ patterning, and growth. A subset of genes expressed in endosperm exhibit imprinted expression, and the correct balance of gene expression between parental alleles is critical for proper endosperm and seed development. We use a transcriptional timeseries analysis to identify genes that are associated with key shifts in seed development, including genes associated with secondary cell wall synthesis, mitotic cell cycle, chromatin organization, auxin synthesis, fatty acid metabolism and seed maturation. We relate these genes to morphological changes in Mimulus seeds. We also identify four endosperm-expressed transcripts that display imprinted (paternal) expression bias. The imprinted status of these four genes is conserved in other flowering plants, suggesting that they are functionally important in endosperm development. Our study explores gene regulatory dynamics in a species with cellular endosperm development, broadening the taxonomic focus of the literature on gene expression in seeds. Moreover, it is the first to validate genes with imprinted endosperm expression in M. guttatus, and will inform future studies on the genetic causes of seed failure in this model system.